High Altitude Disease: Consequences of Genetic and Environmental Interactions - Jin, MD, Guoen; Li, MD, Shenghua; Ge, MD, PhD, Rili; Albert, PhD, Mitchell; Sun, PhD, Yanping (North American Journal of Medicine and Science, 2009)
High altitude disease (HAD) is a pathological effect of high altitude on humans, caused by acute exposure to low partial pressure of oxygen at high altitude. Millions of people who live at, or ascend to, altitudes above 2,500 m, are at risk for acute mountain sickness (AMS) and chronic mountain sickness (CMS). Among these populations, there are distinct patterns of adaptation to the environment, lowlanders are more susceptible to HAD than highlanders when they are exposured to hypoxia, Andean highlanders have higher incidence rate of HAD than Tibetans and Sherpas. People originating from the same sea level have different response to hypoxia. These situations showed that the incidence of HAD has a certain genetic background. With the development of modern research techniques, there is more and more evidences that indicates that the pathogenesis of HAD is associated with some mutant form of hypoxia-related genes, number and function of the genes encoding protein, such as HIF1A,EPO,EDN1,NOS3, and also associated with human leukocyte antigen (HLA)(define it)